Crystalline forms of PVDF fiber filled with clay components along processing steps. Issue 14 (15th December 2015) - Boudriaux, Matthieu; Rault, François; Cochrane, Cédric; Lemort, Guillaume; Campagne, Christine; Devaux, Eric; Courtois, Christian
ABSTRACT: There is a growing interest in the supply of autonomous electronic devices, particularly in the field of smart textiles. Energy harvesting is considered as a clean and renewable alternative technology to reach this objective. One of the methods explored is scavenging the energy from ambient mechanical vibrations by using piezoelectric materials. Due to textile requirements, the development of PVDF based fibers appears to be an interesting solution. However, the amount of its β crystalline form should be as high as possible. PVDF/clay components (modified or unmodified clay as well as organic modifier) containing up to 5 wt % additive are prepared by melt spinning. FTIR and XRD experiments show that the most important factor for obtaining high levels of β crystalline form is to increase the drawing ratio. The results indicate also that an organic modifier (quaternary ammonium salt) influences the crystalline forms and leads to a high ratio of β phases. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43244. Abstract :